2017
DOI: 10.3390/catal7070197
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of CeO2 Nanorods and CeO2 Nanoflakes on Ni–S Alloys in Hydrogen Evolution Reactions in Alkaline Solutions

Abstract: Composite coatings synthesized by different morphologies of CeO 2 in supergravity devices are highly active in hydrogen evolution reactions (HERs). By adding CeO 2 nanoflakes (CeO 2 Nf) or CeO 2 nanorods (CeO 2 Nr), the change in the microstructures of composites becomes quite distinct. Moreover, most Ni-S alloys are attached on the surface of CeO 2 and roughen it compare with pure CeO 2 . In order to make the expression more concise, this paper uses M instead of Ni-S. At a current density of 10 mA/cm 2 , over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…At last, the performance of our N-CeO 2 was compared with previously reported HER catalysts, most of which are CeO 2 -based materials [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. As listed in Table 1 , the overpotential and Tafel slope of N-CeO 2 are superior or comparable to most of the previously developed CeO 2 -based catalysts, even when they are incorporated with other functional substance which may improve their conductivity or directly act as active components.…”
Section: Resultsmentioning
confidence: 99%
“…At last, the performance of our N-CeO 2 was compared with previously reported HER catalysts, most of which are CeO 2 -based materials [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. As listed in Table 1 , the overpotential and Tafel slope of N-CeO 2 are superior or comparable to most of the previously developed CeO 2 -based catalysts, even when they are incorporated with other functional substance which may improve their conductivity or directly act as active components.…”
Section: Resultsmentioning
confidence: 99%
“…The lower onset potential and higher current density from LSV plots in Figure S14a clearly indicated a superior hydrogen evolution reaction over Ce 0.75 Ti 0.25 O 2 compared to CeO 2 . To attain a cathodic current density of 10 mA cm –2 , Ce 0.75 Ti 0.25 O 2 required a overpotential (η 10 ) of 0.88 V, whereas CeO 2 required 0.97 V. The Tafel slope in Figure S14b suggested that the hydrogen generation process over Ce 0.75 Ti 0.25 O 2 complied with the Volmer–Heyrovsky mechanism wherein the release of H 2 is the rate-determining step. The poorer CO 2 reduction over Ce 0.75 Ti 0.25 O 2 would also reflect in the product distribution of the reaction. Therefore, the product selectivities were determined by CPEs under CO 2 saturation at variable potentials for 4 h duration over both the metal oxides.…”
Section: Catalysismentioning
confidence: 95%
“…[ 29 ] Moreover, Ni 3 N and Ni–S alloys, etc., were composited to CeO 2 and both generate good electrocatalytic properties (Figure 1g–i). [ 30–32 ] Therefore, the HER activity and stability of different catalysts including novel metal, transition metals, transition metal phosphides, and transition metal nitrides catalysts are enhanced by compositing CeO 2 since it tends to regulate and optimize the electronic structure of catalyst ( Table 1 ). The optimized hydrogen adsorption free energy caused by adjusting the electronic structure of catalysts leads to a promoted HER performance.…”
Section: Ceo2‐based Electrocatalystmentioning
confidence: 99%